Adoption and non-adoption of potato production through zero tillage with rice straw mulch (PZTM) in coastal Bangladesh - Rahaman, E.H.M.S.; Hossain, M.; Ibrahim, F.; Kawarazuka, N. (2025)
This study examines the adoption and non-adoption of potato production through zero tillage with rice straw mulch (PZTM) in coastal Bangladesh, a region affected by soil salinity and freshwater scarcity. Based on a mixed-methods survey of 2,943 beneficiaries, the report shows that while 43% of farmers adopted the technology at least once, continued adoption declined mainly due to limited access to affordable, high-quality seed. The findings highlight that PZTM improves food security during the dry season, reduces labor and irrigation needs, and supports women’s participation in decision-making. Strengthening local seed systems and collective seed purchasing are identified as key strategies for scaling this climate-smart and regenerative technology.